2017
DOI: 10.1111/icad.12219
|View full text |Cite
|
Sign up to set email alerts
|

Coextinction dilemma in the Galápagos Islands: Can Darwin's finches and their native ectoparasites survive the control of the introduced fly Philornis downsi?

Abstract: The survival of parasites is threatened directly by environmental alteration and indirectly by all the threats acting upon their hosts, facing coextinction. The fate of Darwin's finches and their native ectoparasites in the Galápagos Islands is uncertain because of an introduced avian parasitic fly, Philornis downsi, which could potentially drive them to extinction. We documented all known native ectoparasites of Darwin's finches. Thirteen species have been found: nine feather mites, three feather lice and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The widespread use of pyrethroids has raised concerns globally about nontarget effects on humans and native wildlife (Hu et al., 2019; Ye & Liu, 2019). In the Galápagos Islands, the use of permethrin for controlling P. downsi is contentious because of concerns about its toxicity for nestlings and native arthropods (Bulgarella & Palma, 2017; Causton & Lincango, 2014). Other studies have found sublethal effects of direct exposure of permethrin on nestling growth in the field and in captivity (Bulgarella et al., 2020; López‐Arrabé et al., 2014), and heavy exposure over multiple generations decreases fledging success of captive zebra finches (Bulgarella et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of pyrethroids has raised concerns globally about nontarget effects on humans and native wildlife (Hu et al., 2019; Ye & Liu, 2019). In the Galápagos Islands, the use of permethrin for controlling P. downsi is contentious because of concerns about its toxicity for nestlings and native arthropods (Bulgarella & Palma, 2017; Causton & Lincango, 2014). Other studies have found sublethal effects of direct exposure of permethrin on nestling growth in the field and in captivity (Bulgarella et al., 2020; López‐Arrabé et al., 2014), and heavy exposure over multiple generations decreases fledging success of captive zebra finches (Bulgarella et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that Darwin’s finches produce measurable innate and adaptive immune responses to invasive parasites. Darwin’s finches host other parasitic taxa, such as lice and mites, with which they have longer-standing relationships (reviewed in Bulgarella et al , 2017 ). Therefore, finches could have evolved immune defences against their native parasites, which also cross-react with the novel parasites.…”
Section: Applied Ecoimmunology In Conservation: Case Studiesmentioning
confidence: 99%
“…Considered a largely pristine "living laboratory", Galapagos was declared a UNESCO World Heritage in 1978. The unique marine and terrestrial wildlife and ecosystems have been the center of conservation research and conservation success for over five decades [76][77][78][79][80][81][82][83]; however, governance and management issues that threaten the biodiversity and sustainability of the islands remain [84][85][86], and research priorities such as population growth, climate change, novel pathogens, and invasive species control have been defined as critical to improve the social-ecological fit of conservation strategies in Galapagos [87]. The conservation of Galapagos giant tortoises (Chelonoidis spp) has been largely successful due to a huge reduction in hunting, the eradication of invasive species such as goats and pigs from much of the archipelago, and captive breeding and reintroduction [79,[88][89][90].…”
Section: Case Study: Human-giant Tortoise Interactions In Santa Cruz mentioning
confidence: 99%